Modelagem e controle de dois conversores CC-CC de alto ganho de tensão intercalados baseados na CCTE - Chaves, Breno Bezerra (2019)
This masters dissertation brings a modeling and design methodology for the digital control of a DC-DC High Voltage Gain Interleaved Boost converter, which is based on the Three-State Switching Cell (CCTE). This work aims to ensure current balancing between the parallel modules and between the windings of the Multi-Interphase Transformers (TMIF) of each module, as well as enabling the use of the interleaved converter for nonlinear load applications. This topology has the ability to split the input current and distribute the current efforts between the transformer phases, and it is also suitable for applications requiring high voltage gain from the input to output port. For modeling the plant, a methodology is applied to obtain a reduced order model, resulting in an equivalent Boost converter, which describes the dynamic behavior of the system from the point of view of the TMIFs windings. The current of each winding is then independently controlled using the average current mode control. The control strategy adopted uses four internal loops to balance the currents and an outer loop to regulate voltage on the output DC-link . The control signal at the voltage loop output is then used as the set-point for the current loops. In order to validate the effectiveness of the implemented control, the converter is subjected to step-load variation, phase current unbalance situations and nonlinear load operation. The closed loop simulation results are satisfactory when contrasted with the simulation results for open loop control under same test conditions.